Design and Implementation of Smart Contract in Supply Chain Management Using Blockchain and Internet of Things - Fatima Haider Naqvi; Sundus Ali; Binish Haseeb; Namra Khan; Soomal Qureshi; Taha Sajid; Muhammad Imran Aslam (Engineering Proceedings, 2023)
In this paper, we have presented the design and implementation of a blockchain-based approach for ensuring reliable supply chain management for commodities transported through smart containers. To administer interactions between the sender and receiver, our developed system makes use of the Ethereum blockchain’s smart contract features. Smart containers equipped with Internet of Things (IoT)-enabled sensors are used to monitor shipping conditions to check predefined shipping requirements. Smart contracts on Ethereum are used to automate payments, validate receivers, and give refunds in the case of violation of predefined requirements. We have also implemented our designed front-end decentralized WebApp and wallet that allows the sender and receiver to communicate with Ethereum smart contracts.